INVESTIGATION OF THE HEAT TRANSFER PROCESS IN A SHELL-AND-TUBE HEAT EXCHANGER AND THE EFFECT OF TUBE FOULING LAYER - Sagyngaliyeva, С.Қ.; Tungatarova, М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
Shell-and-tube heat exchangers are widely used in thermal power engineering, the oil and gas industry, and chemical engineering for cooling, heating, and evaporation processes. This study investigates the heat transfer process in a shell-and-tube heat exchanger. In the numerical model, the turbulent flow inside the tubes and in the shell side was described using the Reynolds-Averaged Navier–Stokes (RANS) equations. To close the system of equations and solve the additional unknown turbulent quantities arising from the averaging procedure, the k–ε turbulence model was employed, with its parameters selected based on experimental data. The numerical results were validated against experimental measurements, yielding an average relative error of 1.59–1.68 %, which confirms the accuracy of the model and the correct physical representation of the process. Based on the verified model, fouling formation on the tube surfaces—caused by the deposition of salts, suspended particles, and the accumulation of corrosion products—was investigated. The fouling layer thickness was varied within the range , and a parametric analysis was performed. The results demonstrated that increasing the fouling layer thickness leads to a reduction in the overall heat transfer coefficient, an increase in tube temperatures, and a deterioration of the heat transfer performance. The findings of this study can be used to develop strategies for fouling mitigation, improve the efficiency and design of shell-and-tube heat exchangers, and support energy-saving initiatives in industrial and power-generation systems.